SOCCER PLAYER’S PHYSICAL TRAINING FOR PHYSICAL FUNCTION IMPROVEMENT - Chen,Xi (2022)
ABSTRACT Introduction: Soccer is an intensely competitive sport. With its development and elevation in techniques, athletes’ higher demands for physical fitness, strategy, and tactics are presented. An excellent physical training protocol is essential to achieve these goals. Objective: To study how soccer players can improve their physical function in physical training. Methods: Soccer players from a school were selected as research subjects. Physical training interventions and follow-up tests were performed on soccer players during training. Physical training included a physical function test and a body composition test. Finally, SPSS16.0 software was used for statistical analysis of the obtained data. Results: The mean hemoglobin and red blood cell concentration mean values in the athletes’ final test increased slightly compared to the first test; the difference was insignificant (P>0.05). However, the hematocrit index improved significantly (P<0.01). Conclusion: Physical training can reduce the body fat content in the physical function of soccer players and reduce the weight of soccer players. This physical training mode can be used as a reference standard for the physical training of other high-level soccer teams. Evidence Level II; Therapeutic Studies - Investigating the result.